THE ROLE OF GRATITUDE PRACTICES IN ENHANCING PSYCHOLOGICAL RESILIENCE - Josefa Flores; Isabel Martinez; Sara Hussain (Research Psychologie, Orientation et Conseil, 2026)
Psychological resilience is a crucial factor in overcoming challenges and maintaining mental well-being, particularly in the face of adversity. Recent research suggests that gratitude practices may enhance resilience by fostering positive emotions, reducing stress, and improving overall psychological health. However, the specific mechanisms through which gratitude influences resilience remain underexplored. This study aims to examine the role of gratitude practices in enhancing psychological resilience. The research explores how regular engagement in gratitude exercises can improve individuals' ability to cope with stress and adapt to difficult situations. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. Data were collected from 250 participants, with a focus on measuring gratitude levels, psychological resilience, and stress responses before and after a 4-week gratitude intervention. The Gratitude Questionnaire (GQ-6) and the Resilience Scale for Adults (RSA) were used to assess participants' emotional well-being and resilience. The findings indicated that participants who engaged in gratitude practices reported significantly higher levels of psychological resilience, as well as lower stress levels, compared to those who did not. Gratitude was shown to increase positive emotions and enhance adaptive coping strategies in stressful situations. This study concludes that gratitude practices are effective in enhancing psychological resilience.